2020
DOI: 10.1186/s12884-020-03073-w
|View full text |Cite
|
Sign up to set email alerts
|

Absence of lymphatic vessels in term placenta

Abstract: Background: There has been debate about the existence of lymphatic vessels in placenta. Lymphatic endothelial cell (LEC) markers such as LYVE-1 and podoplanin/D2-40 have been found, although PROX1 has not been detected. The most reliable marker for LECs is the double staining for CD31 and PROX1, which has not been performed yet. Methods: We studied three term placentas and dissected them into three areas: i.) basal plate area, ii.) intermediate area, and iii.) chorionic plate area. We used immunofluorescence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…This prompted us to question whether there may be a lymphatic network within the chorio-allantoic placenta. To date, lymphatic markers have only been investigated on the maternal side of the placenta ( Pawlak et al, 2019 ) and found to be absent in the term human placenta ( Becker et al, 2020 ). We first screened common lymphatic proteins (PDPN, LYVE1, and PROX1) for expression in the mid-late gestation placenta.…”
Section: Resultsmentioning
confidence: 99%
“…This prompted us to question whether there may be a lymphatic network within the chorio-allantoic placenta. To date, lymphatic markers have only been investigated on the maternal side of the placenta ( Pawlak et al, 2019 ) and found to be absent in the term human placenta ( Becker et al, 2020 ). We first screened common lymphatic proteins (PDPN, LYVE1, and PROX1) for expression in the mid-late gestation placenta.…”
Section: Resultsmentioning
confidence: 99%
“…However, venous drainage of the umbilicus was mostly via the abdominal cutaneous veins. Although the pla-centa contains no lymphatic tissues [8], it is likely that thick lymphatic vessels along the umbilical artery drained the umbilical cord at and near the umbilicus. These thick lymphatic vessels are presented in classical textbooks of anatomy, as described by Monie [9].…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and immunophenotype were incompatible with KHE or KLA: positive for vimentin, CD99, and WT1, and negative for CD31, CD34, ERG, D2-40, CD117, HMB45, S100, SMA, calponin, and cytokeratin (AE1/ AE3). The absence of lymphatics in the placenta 7 further ruled against KLA. Infantile fibrosarcoma in the placenta had not been previously reported and was not yet in the differential diagnosis.…”
Section: Case Historymentioning
confidence: 99%